PENGARUH POTENSI DESA, LOKASI DESA, KREATIFITAS KEPALA DESA DAN PARTISIPASI ANGKATAN KERJA TERHADAP KESEJAHTERAAN MASYARAKAT DESA DI KABUPATEN BULELENG - Sundariani, Ni Putu Sri; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The purpose of this study was to analyze the effect of village potential, village location, village head creativity and labor force participation on the welfare of the village community in Buleleng Regency. In this study, the population was all villages in Buleleng Regency, as many as 129 villages. In this study, the sampling technique used was non-probability sampling with purposive sampling. In this research, the analytical technique used is path analysis. Based on the results of the analysis described in the previous chapter, it can be concluded that village potential, village location and creativity of the village head have a positive and significant impact on the level of labor force participation in Buleleng Regency, while Village Potential, Village Location and Creativity of the Village Head have no effect on welfare. village community in Buleleng Regency. The level of labor force participation has a positive and significant impact on the welfare of rural communities in Buleleng Regency.